Citra Perempuan dalam Novel Dompet Ayah Sepatu Ibu karya J.S. Khairen - Sari, Dian Meliya; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2024)
This research aims to discuss: (1) women's self-image and (2) women's social image in the novel Dompet Ayah Shoes Ibu by J.S. Khairen. This type of research is literary research using descriptive methods. The research data is a set of language in the form of the narrator's explanation, the character's behavior and speech. Data was collected by reading and understanding the novel, marking words, phrases, clauses and sentences, and taking an inventory of women's images. The data was analyzed in the stages of identifying and classifying the data, analyzing and interpreting the data, drawing conclusions from the data, and reporting it in the form of a thesis. This research found: (1) women's self-image consists of a physical image: strong like men and having a firm face, and a psychological image: hard worker, determined, optimistic, never gives up, noble-hearted, high spirited, and caring. (2) the social image of women consists of the image in the family: niece, sister, wife, children, and mother and the social image in society: students, friends, teachers, and residents.